INFLUENCE OF VACCINATION CAMPAIGN AGAINST INFLUENZA ON THE MORBIMORTALITY OF OLDER ADULTS BY RESPIRATORY DISEASES IN MINAS GERAIS, BRAZIL - Maia, Carina Santos; Castanheiras, Gisele Guedes Ruas; Montenegro, Lívia Cozer; Pimenta, Adriano Marçal (Journal of Health Care, 2015)
Introduction: Respiratory diseases and their complications have increased in recent decades and figuredas the leading causes of hospitalization for the population aged over 60 years. Objective: To analyze theinfluence of influenza vaccination on the older adults’ morbidity and mortality by respiratory diseases inMinas Gerais, Brazil, between 1992 and 2010. Materials and methods: Descriptive study conductedwith morbimortality and vaccination coverage data, consolidated by the Departamento de Informáticado Sistema Único de Saúde (DATASUS) [Data Processing Department of the Brazilian Unified HealthSystem]. We calculated mortality, lethality, and hospitalization rates. Results: In some years of the analyzedperiod, the vaccination coverage was lower than the targeted, but it was close to it. The pneumoniamortality rate for the age group of 60-64 years had little change during the period. However, for the olderadults with 65 years or more, the mortality rate shows considerable fluctuation. The lethality rate hasincreased over the period for both age groups, but was higher for the older adults with 65 years or more.By analyzing the frequency of pneumonia hospitalization during the period, it has been found that, in1999, this frequency started decreasing, however, for the older adults with 65 years or more, in 2006, thefrequency of hospitalization started to increase again, reaching its highest value in 2010. Conclusion: The vaccination against influenza might decrease the morbimortality, however there are still strategies necessaryto attract the older adults with the focus of improving vaccination adherence.